Ceratiomyxa arbuscula: A White Tubular Myxomycetes in West Java - Hermawan, Rudy; Amalia, Tryanisa Ridla (Biotropika: Journal of Tropical Biology, 2022)
A white tubular Myxomycota is identic to the Ceratiomyxa genus. Ceratiomyxa has five sporangium types such as a simple pillar, fruticulus, arbuscula, filliforme, and porioides. Slime mold as Ceratiomyxa was found in IPB University. The specimen was coded as Tub1. The specimen Tub1 was found on the rotten wood and together colonized the wood as a substrate with other fungi, such as Sphaerobolus stellatus and Lentinus sajor-caju. The morphological observation was conducted, such as sporangium type, sporangium color, spore size, spore shape, and spore position of the sporangium. To identify the species, phenetic analysis was conducted for five species of Ceratiomyxa and Stemonitis fusca as an outgroup. All characters were transferred into binner data. Then, the SAHN cladogram was built using Numerical Taxonomy System (NTSys) software. The SAHN cladogram showed that Ceratiomyxa specimen Tub1 was identified as Ceratiomyxa arbuscula with a 100% similarity coefficient. The morphology supported the identification, such as the shape of arbuscula sporangium and the spore size.